Detecting fraudulent statements in the financial statements An applied study for a group of Saudi companies for the period 2019-2021 - guerfi, Hadjer; chalabi, Amar; kimouche, bilal (Journal of Research in Finance and Accounting, 2025)
The aim of this study is to examine whether Saudi companies practice fraudulent operations when preparing their financial statements and the effect of some factors (listing on financial market, Activity sector, and Covid-19 pandemic). The study included 24 listed and non-listed companies for the period 2019-2021, where the total observations reached 72 observations that classified according to the model of(Beneish, 1999) into fraudulent and non-fraudulent subsamples. The statistical test was conducted using Eviews, based on Multiple leaner regression and indicated statistical indicators on the involvement of Saudi companies in fraudulent operations during the preparation of their financial statements, and that the listing on financial market and the Covid-19 pandemic had has an effect on the level of fraud in the financial statements, while no effect of the activity sector was recorded on the level of fraud in the financial statements.